Evaluation on the efficacy of commonly used Prickly heat talcum powder against Staphylococcus epidermidis in Miliaria rubra - N, Rekha; Austin, Anoop (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Miliaria rubra is an acute inflammatory pruritic eruption of the skin, which is caused by the blockage of sweat glands and retained sweat, which is mainly managed by various prickly heat talcum powders. This study was carried to evaluate the efficacy of Prickly heat talcum powder in Miliaria rubra against Staphylococcus epidermidis. Six popular prickly heat talc samples were collected from the market and evaluated. All the prickly heat talc study results were encouraging and demonstrated efficacy against the test organism and are briefed in detail.